The relationship between the UPPS-P impulsive personality traits and substance use psychotherapy outcomes: A meta-analysis. (1st September 2017) - Hershberger, Alexandra R.; Um, Miji; Cyders, Melissa A.
Highlights: UPPS-P model used to examine impulsive personality in substance use disorder (SUD) treatment. High negative urgency and lack of premeditation related to poorer treatment outcome. Small decreases in sensation seeking and negative urgency through treatment. Great need to integrate impulsive personality into substance use treatment. Abstract: Background: Although impulsive personality traits have been well implicated in substance use disorder (SUD) risk, little work has established how specific impulsive personality traits influence and are influenced by SUD psychotherapy outcomes. The purpose of this meta -analysis was to quantitatively review existing work to examine 1) how impulsive personality traits affect SUD psychotherapy outcomes and 2) reductions in impulsive personality traits during SUD psychotherapy. Methods: Studies were identified by conducting a comprehensive review of the literature. Results: For aim one (k = 6), significant effects were found for lack of premeditation (g = 0.60, SE = 0.30, 95% CI 0.01–1.20; z = 1.99, p = 0.05) and negative urgency (g = 0.55, SE = 0.17, 95% CI 0.22–0.88, z = 3.30, p=0.001), with trait scores related to poorer SUD psychotherapy outcomes. For aim two (k = 10), decreases in sensation seeking (g = −0.10, SE = 0.05, 95% CI −0.20 to 0.004; z = −1.88, p=0.02) and negative urgency (g = −0.25, SE = 0.14, 95% CI −0.53 to 0.03; z = −1.75, p=0.03) during SUD psychotherapy were significant. Conclusions: Overall, our quantitative synthesis suggests that lack of premeditation and negative urgency are related to poorer SUD psychotherapy outcomes. Although negative urgency and sensation seeking are decreasing during SUD psychotherapy, the magnitude of the change is quite small. Overall, we suggest that the measurement and targeting of impulsive personality traits in psychotherapy has strong potential to improve clinical outcomes across SUDs and a wide range of clinical problems and disorders.